2005
DOI: 10.1111/j.1365-2699.2005.01295.x
|View full text |Cite
|
Sign up to set email alerts
|

Zoogeography of the shallow‐water holothuroids of the western Indian Ocean

Abstract: Aim To analyse the zoogeography of the shallow-water holothuroids of the western Indian Ocean (WIO). Based on this analysis we ask to what extent differences in species' ability to disperse across potential barriers provide an explanation for holothuroid zoogeography.Location Shallow-waters (50 m isobaths) of the WIO, extending from Suez to Cape Town and from the coastline of East Africa upward to 65°E.Methods Data for the analysis were obtained from Samyn's (2003) monograph on the shallow-water sea cucumbers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 46 publications
0
30
0
Order By: Relevance
“…Although previous studies in holothurians [16] not resolve the fine pattern within the circumtropical region, subdivisions are evident from taxonomic turnovers. These three putative biogeographic provinces are supported by our present analysis while fine subdivision is further revealed.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Although previous studies in holothurians [16] not resolve the fine pattern within the circumtropical region, subdivisions are evident from taxonomic turnovers. These three putative biogeographic provinces are supported by our present analysis while fine subdivision is further revealed.…”
Section: Discussionmentioning
confidence: 74%
“…Based on the gene flow and distribution pattern obtained, we test the hypothesis whether the biogeography of intertidal barnacles is mainly affected by the major oceanographic patterns and less influenced by geological history in WIO [16].…”
Section: Introductionmentioning
confidence: 99%
“…Rather, each taxon may have its own unique evolutionary history (even congeners may have different histories) with correspondingly unique mechanisms. We additionally include studies focused on an important transition zone along the South African coastline (Bustamante & Branch, 1996;Primo & Vazquez, 2004;Teske, Papadopoulos, Barker, McQuaid & Beheregaray, 2014), studies teasing apart key processes affecting both ancient (Fernandes, Rohling & Siddall, 2006) and more recent migration (Golani, 1993;Kiflawi, Belmaker, Brokovich, Einbinder & Holzman, 2006;Roberts, Shepherd & Ormond, 1992) within and out of the Red Sea, studies focused on the isolating effects of the Arabian Sea upwelling (Kemp, 1998;Schils & Coppejans, 2003), a study using holothuroids as a model to understand zoographical patterns in the Western Indian Ocean (Samyn & Tallon, 2005) and studies that remind us we must not now nor ever forget to consider the ecology of a system when defining biogeographical boundaries (Choat, 2006).…”
Section: Ahti Et Al (2016) Examine Cosmopolitan Wrasses Finding Thamentioning
confidence: 99%
“…Many studies have suggested that multivariate methods can reveal informative biogeographical patterns [33], [34], [35], because one can reduce the inherent complexity of biogeographical data and obtain replicable results [36]. In this study, we analyzed diversity patterns of Sinopotamon using geographical information systems (GIS) and identified areas of endemism (AOEs) using a combination of parsimony analysis endemicity (PAE) and clustering analysis.…”
Section: Introductionmentioning
confidence: 99%